Antifungal activity of green synthesized selenium nanoparticles and their effect on physiological, biochemical, and antioxidant defense system of mango under mango malformation disease - Muhammad Shahbaz (772838) (2023)
Plant extract-based green synthesis of nanoparticles is an emerging class of nanotechnology that has revolutionized the entire field of biological sciences. Green synthesized nanoparticles are used as super-growth promoters and antifungal agents. In this study, selenium nanoparticles (SeNPs) were synthesized using Melia azedarach leaves extract as the main reducing and stabilizing agent and characterized by UV–visible spectroscopy, scanning electron microscopy (SEM), X-ray diffraction (XRD), energy-dispersive X-ray (EDX), and fourier transform infrared spectrometer (FTIR). The green synthesized SeNPs were exogenously applied on Mangifera indica infected with mango malformation disease. The SeNPs at a concentration of 30 μg/mL were found to be the best concentration which enhanced the physiological (chlorophyll and membrane stability index), and biochemical (proline and soluble sugar) parameters. The antioxidant defense system was also explored, and it was reported that green synthesized SeNPs significantly reduced the biotic stress by enhancing enzymatic and non-enzymatic activities. In vitro antifungal activity of SeNPs reported that 300 μg/mL concentration inhibited the Fusarium mangiferae the most. This study is considered the first biocompatible approach to evaluate the potential of green synthesized SeNPs to improve the health of mango malformation-infected plants and effective management strategy to inhibit the growth of F. mangifera. Other Information Published in: PLOS ONE License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1371/journal.pone.0274679